Comparison of Congruent Dynamic Econometric Model Forecasts and SETAR Model Forecasts - Kufel, Paweł (Porównanie jakości prognoz zgodnego dynamicznego modelu ekonometrycznego z prognozami opartymi na modelach SETAR, 2010)
The paper presents dynamic congruent linear econometric model as a tool for forecasting nonlinear relationships between economic processes. The aim of this paper is comparison of forecast errors based on dynamic congruent model and SETAR class models. The root square mean errors of linear and nonlinear are compared. Analysis is based on simulation. Basing on estimated models, forecast is built and forecast errors are calculated. Simulations assume different combinations of parameters: number of observations, scale of disturbance, relations between processes, type of nonlinearity between generated processes and others. Conclusions and remarks are formulated.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 91, s. 76-83
Keywords: dynamic congruent model; SETAR models; nonlinear relationship